Formulasi mie ikan patin dengan rasio tepung terigu dan pasta ubi jalar ungu berbeda sebagai pangan fungsional - Cahyaning Rini Utami; Sulkha Mafaza (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2023)
One of the most popular processed foods is noodles. Making noodles with high protein ingredients can be from catfish. As an alternative to noodles as a functional food, catfish noodles made with wheat flour and sweet potato paste are prepared. The goal of this research is to analyze the results of adding sweet potato and wheat flour proportions on the chemical and organoleptic properties of catfish noodles and to establish the optimum ratio formula for doing so. The study's methodology was a CRD (Completely Randomized Design), with four treatments : F1 (1000g wheat flour), F2 (750g wheat flour: 250g sweet potato pasta), F3 (500g wheat flour: 500g sweet potato pasta), and F4 (250g wheat flour: 750g sweet potato pasta). Each treatment was carried out 3 times in a row, so 12 trials were obtained. The analysis of sweet potato catfish noodles products includes levels of antioxidant, water, and carbohydrate content, The organoleptic analysis observed color, taste, aroma, and texture. The best formulation on research results was found in the F2 treatment (750g of wheat flour:250g of sweet potato paste) with characteristics: water content of 5.4%, carbohydrate content of 65.6%, antioxidant AEAC content: 61 mg/g, and organoleptic evaluations of color 3.53 (like), taste 3.47 (somewhat like ), scent 3.93 (like), and texture 3.70 (like).